Main controlling factors and predictive models for the study of the characteristics of remaining oil distribution during the high water-cut stage in Fuyu oilfield, Songliao Basin, China. Issue 1 (January 2018) - Sun, Mengsi; Liu, Chiyang; Feng, Congjun; Zhang, Ge
The distribution of remaining oil is affected by a number of geological and engineering factors. However, previous studies have mainly focused on the effect of a certain factor or some factors on the distribution of remaining oil. Therefore, this research considers subaqueous distributary channels of Fuyu oil layer in the Fuyu oilfield as a case with following investigations: analysis of the controlling effects of micro-structure, sedimentary micro-facies, single sand body stacking, architecture elements, flow units, well patterns and injection–production relationships on the distribution of remaining oil. Using the coupled effects of multi-factors method, five models of the remaining oil distribution are established as follows: model one includes micro-structure, sedimentary micro-facies, and injection–production relationship; model two includes micro-structure, sedimentary micro-facies, single sand body stacking; model three includes the secondary micro-facies, flow units, and well pattern; model four includes sedimentary micro-facies, single sand body, and injection–production relationship; and model five includes sedimentary micro-facies, architecture elements, flow units, and injection–production relationship. These five models are effective in the study of remaining oil in Fuyu oilfield and can also have a certain example for the other maturing oilfield.